Wheelchair tiedown and occupant restraint system issues in the real world and the virtual world: combining qualitative and quantitative research approaches. - Wolf PJ; van Roosmalen L; Bertocci GE (Assistive Technology)
The Americans with Disabilities Act requires that transit providers accommodate passengers who use 'common wheelchairs' when traveling in a motor vehicle. Wheelchair tiedown and occupant restraint systems are commonly used to secure wheelchairs and restrain occupants in fixed-route and demand route transit vehicles. Throughout the 17 years since the Americans with Disabilities Act has been in effect, transit providers have complained about the usability of wheelchair tiedown and occupant restraint systems, and improper securement has been linked to injuries among wheelchair users during 'nonimpact incidents.' This research study explored the use of wheelchair tiedown and occupant restraint systems in actual practice and the potential risks of misuse to wheelchair-seated individuals. The qualitative research conducted in this study revealed that improper wheelchair securement (i.e. using less than four tiedown straps) can be fairly common practice in fixed-route transit. In addition, preliminary computer simulations show that improper wheelchair securement in emergency driving conditions may place wheelchair occupants at a greater risk of injury. It should be noted, however, that this is a pilot study and has its limitations. For example, qualitative data were gathered from one metropolitan area transit provider across a limited range of vehicle and wheelchair types. Additionally, the computer simulation model used in this study was originally validated for impact situations.